(3CUhd GdEjQGOGJ GdeGdjI GdYGeI aj GdacQ GdeGdj GdESdGej (B/s - (3YfGjI, ZGRjs ((3GdEScfOQjI(B: s (3eDSSI THGH GdLGeYI(B, s, 2006)
(3COdI eTQhYjI GdEjQGOGJ GdeGdjI GdYGeI hGdedcjI GdYGeI GdLeGYjI(B-(3GdEjQGOGJ GdeGdjI GdYGeI GdOhQjI(B-(3GdEjQGOGJ GdeGdjI GdYGeI ZjQ GdOhQjIs
(3jhLO faS GdYfhGf eY SfI fTQ eNJdaI(B((3SfI(B2006)s
Keywords: (3GdGjQGOGJs; (3GdeGdjI GdYGeIs